Stratigraphy of the Vulcanodon type locality and its implications for regional correlations within the Karoo Supergroup. (January 2018) - Viglietti, Pia A.; Barrett, Paul M.; Broderick, Tim J.; Munyikwa, Darlington; MacNiven, Rowan; Broderick, Lucy; Chapelle, Kimberley; Glynn, Dave; Edwards, Steve; Zondo, Michel; Broderick, Patricia; Choiniere, Jonah N.
Abstract: Vulcanodon karibaensis is one of the earliest-branching members of Sauropoda and a forerunner of the largest terrestrial animals ever to have lived. Its stratigraphic position has most recently been given as Toarcian (latest Early Jurassic), making it a contemporary of the northern African taxon Tazoudasaurus, but some literature suggests that it may be considerably older. This uncertainty obscures our understanding of the timing of major sauropod evolutionary events, such as the onset of the major body size increases that characterize the clade. To improve constraints on the geological age of Vulcanodon, we revisited the type locality and collected new, higher precision stratigraphic and sedimentological data. Our results show that Vulcanodon is from lower in the stratigraphy than previously documented, lying within the uppermost Forest Sandstone rather than the interbedded sandstones of the Batoka Basalt Formation. Sedimentological data suggest that the upper part of the Forest Sandstone correlates with the Clarens Formation of the main Karoo Basin, implying that Vulcanodon is likely Sinemurian–Pliensbachian in age, and potentially ∼10–15 million years (Ma) older than previously thought. Highlights: We assessed the provenance of the oldest true sauropod Vulcanodon karibaensis. Type locality of Vulcanodon is the upper Forest Sandstone in Mid-Zambesi basin. Vulcanodon is thus likely 10–15 Million years older than originally hypothesized. This closes the stratigraphic gap between Vulcanodon and basal sauropodomorphs.